Development of Structural Mediation Model of Innovative Strategy, Employees' Job Performance and Technology for UAE Government Sector - Abdulla Lari, Mohamed Ahmed Darwish; Abdul Hamid, Norhadila; Abdulla Lari, Darwish Ahmed Darwish (International Journal of Sustainable Construction Engineering and Technology, 2020)
This study established a relationship of innovations and employees' job performance in the government sector and also the mediating effect of technology towards the relationship. It adopted quantitative approach where data was collected through questionnaires survey and analyzed statistically. The questionnaire survey utilized simple random sampling methods among UAE government employees. A total of 300 questionnaires were distributed randomly and 265 were returned indicates 88.3% response rate. The collected data was then used to develop and assess SEM-AMOS mediation model. The results found that all the direct relationships reported a positive effect. It also found that the innovation dimension constructs and technology mediating construct having explained 84% variation in employees' job performance constructs. For indirect/mediation effect, it was found that technology does not show any mediation effect on the relationship between innovation and job performance constructs.  This implies that technology does not mediate the relationship between innovation strategies and the employees' job performance. It also implies that for an effective employees' job performance core attention to building and managing an innovation approach is required in the UAE government sector. Thus, innovation strategies give more influence to employees' job performance in the government sector through the distinctive capabilities of UAE ministry employees.